Target capital structure and speed of adjustment: Panel data evidence on Malaysia Shariah compliant securities - Haron, Razali; Ibrahim, Khairunisah (International Islamic University Malaysia, 2012)
Islamic Capital Market (ICM) in Malaysia has expanded at an average rate of 13.6% per annum over the ten year period between 2000 and 2010. The size of Malaysia’s ICM is expected to expand at the average rate of 10.6% per annum to reach RM 2.9 trillion by 2020. In line with its future expansion, Shariah compliant securities are and will continue to be one of the important elements in ICM. Motivated by this fact, this study intends to explore the dynamic aspect of capital structure among Shariah compliant firms. The study finds that there exists target capital structure for Shariah compliant firms in Malaysia with both firm specifics and country specific factors playing important roles. Found to be under-adjust these firms readjust in a rapid speed of adjustment. Such rapid adjustment towards target leverage suggests the existence of dynamic trade-off theory. By employing a robust econometric model (GMM),this study contributes to the literature by examining the corporate financing behaviour of Shariah compliant firms in Malaysia ICM.